Characterization of the small RNAs carried by outer membrane vesicles produced by hlyF-positive Shiga toxin-producing Escherichia coli - Giorgia Barbieri; Giorgia Barbieri; Alessia Stefano; Agostina Pietrantoni; Federica Fratini; Serena Cavallero; Rosangela Tozzoli; Paola Chiani; Arianna Boni; Stefano Morabito; Valeria Michelacci (Frontiers in Cellular and Infection Microbiology)
Shiga toxin (Stx)–producing Escherichia coli (STEC) harboring virulence determinants of Extraintestinal pathogenic E. coli (ExPEC) are currently emerging in Europe as a cause of severe disease. Among the ExPEC features identified in STEC, the gene hlyF is associated with an augmented production of Outer Membrane Vesicles (OMV). OMVs produced by E. coli strains have been shown to deliver toxins and small RNAs, but information on the latter genetic component is still scanty. We investigated the small RNAs contained in the OMVs produced by two hlyF-positive STEC strains producing Stx2 belonging to O26:H11 and O80:H2 serotypes, isolated from a human case of Hemolytic Uraemic Syndrome (HUS) and from a milk sample, respectively. The OMVs were purified from overnight cultures using two sequential ultracentrifugation steps at 100.000 and 200.000 x g of 2h each. The OMVs collected were analyzed by Nanoparticle Tracking Analysis (NTA) and Electron Microscopy (EM) to define their morphology, size and concentration. The whole genome sequences of the two test strains and three additional hlyF-positive STEC strains were analyzed to identify sequences of small RNAs. Specific Real Time PCR assays were deployed to detect the small RNAs within OMVs. The EM and NTA characterization confirmed the presence of spherical particles, and showed that a cleaner preparation was obtained after the second step of ultracentrifugation (200.000 x g). We identified the sequences of 27 putative small RNAs present in the genome of hlyF-positive STEC strains and absent in that of a non-pathogenic E. coli. Nine of them were identified and quantified in the OMVs produced by the two test strains. A regulatory role in bacterial DNA replication, integration and in stress-response was hypothesized for the identified small RNAs, some of which encompassing all the domains of life. STnc_100 was the only small RNA identified in the OMVs produced by both strains. Interestingly, a copy of STnc_100 sequence is harbored downstream the stx2 operon carried by Stx2-encoding phages in both the strains and has a complementarity region for stxB gene, suggesting a modulation in Stx production or release. Our results indicate that OMVs release may exert regulatory functions, putatively influencing the crosstalk with the host and the gut microbiota during the infection process.